2012
DOI: 10.1103/physrevlett.108.106103
|View full text |Cite
|
Sign up to set email alerts
|

Commensurate Registry and Chemisorption at a Hetero-organic Interface

Abstract: We present evidence for a partly chemisorptive bonding between single monolayers of copper-II-phthalocyanine (CuPc) and 3,4,9,10-perylene-tetracarboxylic-dianhydride (PTCDA) that are stacked on Ag(111). A commensurate registry between the two molecular layers and the substrate, i.e., a common crystallographic lattice for CuPc and PTCDA films as well as for the Ag(111) surface, indicates that the growth of the upper layer is dominated by the structure of the lower. Photoemission spectroscopy clearly reveals a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
109
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(126 citation statements)
references
References 27 publications
15
109
2
Order By: Relevance
“…The key role of the molecule/surface interaction for the formation of the bicomponent assembly is exemplified by the co-deposition of CuPc and PTCDA. 241 The mixing is not favored, and separated islands are formed due to a stronger adsorption interaction of the two molecules on Ag(111) than for that of CuPc/PTCDA. The resulting system consists of large, densely packed CuPc domains condensed on a compact PTCDA monolayer on Ag(111), whereas one observes a highly ordered mixture of these two molecules on Cu(111).…”
Section: Comparison Between Adsorption On Noble Cu Ag and Au Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The key role of the molecule/surface interaction for the formation of the bicomponent assembly is exemplified by the co-deposition of CuPc and PTCDA. 241 The mixing is not favored, and separated islands are formed due to a stronger adsorption interaction of the two molecules on Ag(111) than for that of CuPc/PTCDA. The resulting system consists of large, densely packed CuPc domains condensed on a compact PTCDA monolayer on Ag(111), whereas one observes a highly ordered mixture of these two molecules on Cu(111).…”
Section: Comparison Between Adsorption On Noble Cu Ag and Au Surfacesmentioning
confidence: 99%
“…410 In these systems, the deposition of a second layer of molecules on the first self- 428,429 showed that upon deposition of CuPc on a monolayer of PTCDA/Ag(111), the enhanced charge transfer from the substrate to the bilayer did not involve CuPc electronic states (the second layer) but only the PTCDA layer with a strengthening (shortening) of the PTCDA-Ag (111). 241 The authors suggested that the second layer of CuPc molecules can be treated as a polarizable medium, enabling an additional screening mechanism assisting the screening by the surface image charges. So far, this exploration has been essentially limited to commercially available molecules, but it is likely that this field will reveal its full potential with tuned and customized molecules.…”
Section: Organic Thin Filmsmentioning
confidence: 99%
“…1 Yet, the highest possible accuracy of LEED instruments is typically not reached due to the neglect of systematic errors which can actually be accounted for. In certain cases, for instance, when the superposition of spots ascertains a commensurate registry, 2 or when the absence of specific diffraction spots suggests special symmetry properties, 3 the epitaxial matrix (and hence the unit cell parameters) may be given with a better confidence level than what would generally be achievable without such helpful specifics. However, if the structure of a non-commensurate (i.e., point-on-line, line-on-line, or incommensurate) [4][5][6] overlayer on a known substrate or the structure of a totally unknown sample is to be measured accurately, one has to rely on the visualization of the k-space of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the structure of a non-commensurate (i.e., point-on-line, line-on-line, or incommensurate) [4][5][6] overlayer on a known substrate or the structure of a totally unknown sample is to be measured accurately, one has to rely on the visualization of the k-space of the specimen. Owing to the characteristics of the various experimental setups and/or the recording of the diffraction patterns, image distortions will generally occur not only in LEED 2,[7][8][9][10] but also in other diffraction methods. [11][12][13][14] Depending on the purpose of investigation, for example, when measuring lattice parameters and strain or when classifying the coincidence of an epitaxial organic layer, the distortions must be corrected in order to make these measurements meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore interesting to examine whether a mixed, heteromolecular phase between the two can be prepared, and how the differences in the intermolecular and molecule-substrate interactions affect the geometric and electronic properties of the film. Although technologically relevant, such heteromolecular adsorbate systems have rarely been systematically investigated in the literature so far [32][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
mentioning
confidence: 99%